How Perspectives on Language Development Affect English as a Foreign Langage Teaching (Global Journal of Human-Social Science, 2012)
Based on the review of three perspectives of language development this paper is aimed to focus on interactionalist s position and provides insights into the influences of it on English as a foreign language teaching EFLT
Keywords: Behaviorism Innatism Interactionalist’s position